PENGARUH KEPEDULIAN ORANG TUA TERHADAP PEMBINAAN AKHLAK SISWA MTs. No.12 BINGKARONGO KABUPATEN BULUKUMBA - wani, Nirwani; Mawardi , Amirah; Ferdinan (Jurnal Riset Guru Indonesia, 2025)
This study aims to find out how parents care about MTs students. No. 12 Bingkarongo, Bulukumba Regency, to find out the Moral Development of MTs Students. No. 12 Bingkarongo, Bulukumba Regency, and to find out whether there is an influence of parental concern on the moral development of MTs students. No. 12 Bingkarongo, Bulukumba Regency. This research uses a quantitative method, namely research in the form of numbers analyzed statistically using a correlational approach. The technique used in sampling is purposive sampling in which the sample is determined by the researcher. The population in this study were students of class VII MTs. No. 12 Bingkarongo, Bulukumba Regency and the sample consisted of two class VII, totaling 40 students and parents of MTs students. No. 12 Bingkarongo, Bulukumba Regency. The results showed that from the percentage of filling out the questionnaire about the concern of MTs students' parents. No. 12 Bingkarongo, Bulukumba Regency, it can be concluded from 40 respondents that they are in the moderate category of caring for parents of children, namely 22 people (55%), while the Moral Development of MTs students. No. 12 Bingkarongo, Bulukumba Regency, it can be concluded that from 40 respondents, 28 people (70%) were in the category of moderate moral development. Then, in statistical testing the simple linear regression test is Ŷ = a + bX, a = the constant number of Unstandardized Coefficients the value is 37.323 and b = the regression coefficient number the value is 0.418. This figure means that for every 1% addition to the level of parental concern (X), moral development (Y) will increase. Thus, it can be concluded that the higher the parental concern, the more it affects the moral development of MTs students. No. 12 Bingkarongo Bulukumba Regency. Keywords: Parental Concern; Moral Development.